Long-term Healthcare of People with Disorders of Sex Development: Predictors of Pubertal Outcomes of Partial Androgen Insensitivity Syndrome – Authors' Reply - Lek, N. (Elsevier B.V., 2021)
10.1016/j.ebiom.2018.10.035